Penilaian portofolio pada pembelajaran IPA di MI - PGMI, Munadiyal Khairi; Jelita, Jelita; Suhelayanti, Suhelayanti (azkiya, 2022)
This study aims to determine the implementation of portfolio assessment in science learning at MIN 5 Aceh Tamiang. This research is descriptive qualitative. The methods used for data collection include observation, interviews, and documentation. Data reduction, data presentation, and data verification are theoretical techniques used in data analysis by Miles and Huberman. The results of the study indicate that the teaching and learning process using portfolios has been going well because it is in accordance with the rules that apply in madrasas and teachers have used K13 but at the time of portfolio assessment, there is still one indicator (observation sheet) that has not been implemented properly this is because the teacher does not understand how to make an observation sheet in ecosystem material